Biological activity of Gomphrena elegans Mart. var. Elegans (Amaranthaceae) - Mahmoud, T. S. [UNESP]; Marques, M. R. [UNESP]; Leite, C. B. [UNESP]; Antonio, M. M. [UNESP]; Mahmoud, A. S. [UNESP]; de Souza, A. P. [UNESP]; de Lima, D. P. [UNESP]; de Oliveira, J. E. [UNESP] (My University, 2011)
In this study, we evaluated the allelopathic, insecticidal and fungicidal activities of 16- extracts (different polarities) of Gomphrena elegans Mart. (Amaranthaceae). The potential allelopathic of extracts of G. elegans obtained from leaves and stems were most inhibitory to the germination and seedlings growth L. sativa, in general, the extracts stimulated the growth of seedlings. The insecticidal activity of extracts were evaluated using ten g of wheat sprayed with 1 mL of each extract at 10% (w/v), the grains were placed in containers with 20 Sitophilus zeamais adults and the assessments were made at 5 and 10 days. The most active were the hexane, chloroform and aqueous extracts; however, they showed no insecticidal activity against Aedes aegypti. All extracts were evaluated for antifungal activity against the plant pathogenic fungus Cladosporium sphaerospermum using the direct bioautography. The most active was the aqueous extract of adventitious roots.
Keywords: Aedes aegypti; Allelopathic activity; Bioautography; Cladosporium sphaerospermum; Fungicidal; Germination; Gomphrena elegans; Insecticidal activity; Lactuca sativa; Seedling growth; Sitophilus zeamais; Wheat